Investigation of Dynamic Process Planning using Computer Simulation "Arena" - Umnutkittikul, Pramote (2008)
Due to the dynamic fluctuation of global market and customer demands, manufacturing firms are facing difficulties in rapidly responding to market changes. Many firms are under significant pressure to produce low cost, high quality products that can compete in the world marketplace. It might be useful if the process plan could be dynamically modified to consider the current state in the manufacturing shop floor. Thus, the concept of integration of process planning and scheduling function has been established so as to help the firms to handle an unstable market.